Prediction of Heavy Metal Contamination from Landfill: Lead and Chromium - Budihardjo, Mochamad Arief; Chegenizadeh, Amin; Nikraz, Hamid (AENSI Publisher, 2014)
Leachate from unsorted solid waste landfill usually contains a variety of hazardous compounds including heavy metals such as lead (Pb) and chromium (Cr) which may contaminate soil and groundwater in the area surrounding the landfill. To minimize leachate contamination, there must be an impermeable liner beneath the landfill which functions as a leachate barrier. However, there is always the possibility for leachate to seep through the barrier and migrate to the soil and groundwater surrounding the landfill. It is useful for solid waste landfill management authorities to be able to predict the potential for leachate migration to the subsoil during landfill operations and after closure. This research aims to simulate the migration of heavy metal contaminants from a landfill area based on the initial Pb and Cr concentrations at the bottom of the landfill. This research also estimates the Pb and Cr concentration in soil at various depths beneath the landfill over 12 years. The concentrations of both Pb and Cr dropped significantly by more than 70% of their initial concentration when passing through the impermeable liner. Meanwhile, the predicted accumulated concentration of Pb and Crin the subsoil seemed to increase slightly during the 12 years of the simulation. Results also indicated that the Pb and Cr concentrations in all landfill layers under the impermeable layer tend to increase significantly during the first five years of the simulation. Based on the initial concentrations, it was predicted that both of these contaminants could potentially contaminate groundwater surrounding the landfill.